Efeito de diferentes concentrações de conservantes alimentícios no crescimento in vitro de fungos termorresistentes e bactérias patogênicas. - Lima-coelho, Sheyla Ferreira (2008)
The foods are excellent nutrient sources for a wide variety of microorganisms, such as filamentous fungi and yeast or bacteria. They are therefore vehicle for a number of infectious diseases. So the man has sought to prevent such proliferation microbial, and maintain the integrity of the product to be sold or consumed, through physical and chemical barriers. To reduce the risk of multiplication of microorganisms and the consequent deterioration of food, the industries are using, in addition to heat treatment, increasingly, chemical additives (preservatives). Among them, sulphur dioxide, sorbic acid and benzoic acid, and derivatives of them, have been employed in the steps of processing. Thus, seeking to provide subsidies to reduce the use of inadequate quantities of preservatives in the food industry, and therefore unfit to ingestion by the population, it was determined in this work the minimum concentrations of sodium metabisulphite, sodium benzoate and sorbate, potassium necessary for the inhibition of the development of heat-resistant fungi, such as Byssochlamys fulva, Neosartorya fischeri and Talaromyces flavus, and of bacteria, such as Salmonella Enteritidis, S. Typhimurium, Escherichia coli and Bacillus cereus in vitro. The growth-media used were Potato-Dextrose-Agar (PDA) and Tripton- Soybean-Agar (acidified with citric acid, pH 3.5 and 5), for tests with fungi and bacteria, respectively. To these media were added the preservatives in different quantities, in order to obtain concentrations of 100, 150, 200, 250, 300, 400, 500, 600, 700, 800 and 1000 mg.L-1 of them. After inoculation and incubation (28 and 30 ± 2 ° C, in the dark), it was observed that the lowest concentrations of sodium metabisulphite showed greater efficiency in inhibiting the growth of all microorganisms, in comparison with the other preservatives tested in vitro. The lowest concentrations of sodium benzoate, on the other hand, were more effective in inhibiting bacterial growth. Already the potassium sorbate showed greater action to combat the heat-resistant fungi.